Enhancing the efficacy of immunotherapy using radiotherapy - Synat Keam; Suki Gill; Martin A Ebert; Anna K Nowak; Alistair M Cook (Clinical & Translational Immunology, 2020)
Abstract Recent clinical breakthroughs in cancer immunotherapy, especially with immune checkpoint blockade, offer great hope for cancer sufferers – and have greatly changed the landscape of cancer treatment. However, whilst many patients achieve clinical responses, others experience minimal benefit or do not respond to immune checkpoint blockade at all. Researchers are therefore exploring multimodal approaches by combining immune checkpoint blockade with conventional cancer therapies to enhance the efficacy of treatment. A growing body of evidence from both preclinical studies and clinical observations indicates that radiotherapy could be a powerful driver to augment the efficacy of immune checkpoint blockade, because of its ability to activate the antitumor immune response and potentially overcome resistance. In this review, we describe how radiotherapy induces DNA damage and apoptosis, generates immunogenic cell death and alters the characteristics of key immune cells in the tumor microenvironment. We also discuss recent preclinical work and clinical trials combining radiotherapy and immune checkpoint blockade in thoracic and other cancers. Finally, we discuss the scheduling of immune checkpoint blockade and radiotherapy, biomarkers predicting responses to combination therapy, and how these novel data may be translated into the clinic.